2021
DOI: 10.1016/j.celrep.2021.109317
|View full text |Cite
|
Sign up to set email alerts
|

Structure of the TELO2-TTI1-TTI2 complex and its function in TOR recruitment to the R2TP chaperone

Abstract: Highlights d TELO2-TTI1-TTI2 (TTT) forms a direct complex with RUVBL1-RUVBL2 (R2) d TTT interacts with two consecutive DII domains in the heterohexameric R2 ring d TTT inhibits R2 ATPase and antagonizes RPAP3/Tah1p-PIH1D1/Pih1p engagement d TTI1-TTI2 binds the kinase region of mTOR but does not inhibit its catalytic activity

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
37
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(37 citation statements)
references
References 46 publications
(112 reference statements)
0
37
0
Order By: Relevance
“…The R2TP complex has been shown to stabilize client proteins belonging to the phosphatidylinositol 3-kinase-related kinase (PIKK) family, such as mTOR, ATM, ATR, DNA-PKcs, and SMG-1, via interaction with the TTT complex (TELO2-TTI1-TTI2) (Cloutier et al, 2017;Horejsi et al, 2010;Kamano et al, 2013;Pal et al, 2021). R2TP is also involved in the assembly of the TSC complex (TSC1-TSC2-TBC1D7), a regulator of mTORC1, U5 snRNPs and L7Ae RNPs (Cloutier et al, 2017;Malinova et al, 2017;Mir et al, 2015), and RNA polymerase II (Boulon et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…The R2TP complex has been shown to stabilize client proteins belonging to the phosphatidylinositol 3-kinase-related kinase (PIKK) family, such as mTOR, ATM, ATR, DNA-PKcs, and SMG-1, via interaction with the TTT complex (TELO2-TTI1-TTI2) (Cloutier et al, 2017;Horejsi et al, 2010;Kamano et al, 2013;Pal et al, 2021). R2TP is also involved in the assembly of the TSC complex (TSC1-TSC2-TBC1D7), a regulator of mTORC1, U5 snRNPs and L7Ae RNPs (Cloutier et al, 2017;Malinova et al, 2017;Mir et al, 2015), and RNA polymerase II (Boulon et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…How R2TP deals with a diversity of clients is still not well understood, but it has been suggested that ‘adaptor’ proteins contribute to put together the chaperone with specific clients. This model is best characterized for the assembly of mTOR complexes where a TELO2-TTI1-TTI2 (TTT) complex serves to bring mTOR to R2TP ( 11 , 45 ). For U5 snRNP, both ZNHIT2 and ECD have been proposed to function as linker between PRPF8 and R2TP ( 3 , 4 , 20 , 26 ).…”
Section: Resultsmentioning
confidence: 99%
“…Some of these factors could function as adaptor proteins or scaffolds connecting specific clients to the chaperone, while others could perform other, yet unknown, regulatory functions specific to each client. For example, the TTT complex acts as a scaffold between R2TP and clients during the biogenesis of the kinases of the PIKK family, but it also regulates the ATP hydrolysis and some of the interactions taking place within the R2TP complex ( 11 ). Our results suggest that ZNHIT2 could be part of a larger complex containing other regulatory subunits together with PRPF8 and R2TP.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Tti2, together with its binding partners, Tti1 and telomere maintenance 2 (Telo2) protein, form the Triple T (TTT) complex [ 60 ], which associates with a number of molecular chaperones, including Hsp90, Hsp70, Hsp40, and the R2TP/prefoldin-like complex [ 61 , 62 ]. Interaction of TTT with R2TP modifies ATPase activity of R2TP components, RUVBL1-RUVBL2 [ 63 , 64 ]. TTT binds to nascent peptides of PI3K-related protein kinases (PIKK) and delivers them to the R2TP chaperone, thereby acting as a scaffold adaptor and a critical regulator of PIKK abundance in mammalian and yeast cells [ 60 , 62 67 ].…”
Section: Discussionmentioning
confidence: 99%